201k views
3 votes
Let f(x) = (4x^2 - 11)^3 and g(x) = 4x^2- 11.

Given that f(x) = (hºg)(x), find h(x).
Enter the correct answer.

User AbuNassar
by
4.7k points

2 Answers

0 votes

Answer:

the person on top is correct

Explanation:

Let f(x) = (4x^2 - 11)^3 and g(x) = 4x^2- 11. Given that f(x) = (hºg)(x), find h(x-example-1
User TotoroTotoro
by
4.9k points
2 votes

Answer:


\large\boxed{h(x)=x^3}

Explanation:


f(x)=(4x^2-11)^3\\\\f(x)=(h\circ g)(x)=h\bigg(g(x)\bigg)\to\text{exchange x to}\ g(x)=4x^2-11\\\\f(x)=(\underbrace{4x^2-11}_(g(x)))^3=\bigg(g(x)\bigg)^3=h\bigg(g(x)\bigg)\\\\\text{Therefore}\ h(x)=x^3

User Alvherre
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.